Medical educator teaching habits: origins, decisions, and strategies—a phenomenological inquiry (METHODS-PI) - Joshua Moen; Chloe Shuck (Discover Education)
Abstract In recent decades, medical education has been grappling with two significant challenges: the increasing prevalence of burnout among learners at all levels and the concerning trend of industry bias, low-quality evidence, and expert-based opinion driving clinical practice guidelines. To address these issues, a critical evaluation of the medical education and training system is necessary. Utilizing the Socioecological Model (SEM) as a framework, this study employed a phenomenological approach to investigate the methods, habits, decisions, origins, and strategies of medical educators. The aim was to identify the core guiding principles that shape the ecosystem of medical education and training. Semi-structured interviews were conducted with medical educators, and thematic analysis revealed three common themes. First, the irreplaceability of physician educators, found at the heart of the medical education training system, was a central theme. Second, all interviewed educators expressed a desire to enhance the educational environment, drawing upon their current and past training experiences to inform their teaching methods. Tacit knowledge gained from personal experience, years of clinical practice, peer relationships, and mentors played a significant role in shaping their teaching principles. Third, while the goal of improving the educational environment was universal, educators with more formal pedagogical training advocated for more drastic changes and system overhaul, while those without formal training focused on making improvements within the existing framework. The reliance of most physician educators on past experience as a guide for education highlights the sociocultural reproduction and pedagogical inertia prevalent in the 21st-century medical education and training system. Integrating tacit knowledge with formal pedagogy has the potential to impact each level of the hierarchy within the SEM of medical education. By operating beyond the confines of the current system, educators can foster innovation, growth, and critiques that may help alleviate burnout and provide learners with opportunities to challenge current evidence-based practices. This study emphasizes the need for a critical evaluation of the pedagogical theories at the center of the medical education system.